A Novel Algorithm to Identify Predictors of Treatment Response: Tapentadol Monotherapy or Tapentadol/Pregabalin Combination Therapy in Chronic Low Back Pain? - Otto, Jan C.; Forstenpointner, Julia; Sachau, Juliane; Hüllemann, Philipp; Hukauf, Martin; Keller, Thomas; Gierthmühlen, Janne; Baron, Ralf (Frontiers in Neurology, 2019)
Purpose: For treatment of severe chronic low back pain high dose monotherapies or drug combinations are used to achieve sufficient analgesia. In order to demonstrate an alternative for an empirical treatment approach the authors’ primary aim was to present an algorithm for the objective identification of treatment predictors. Additionally, the study identified baseline-characteristics in chronic low back pain patients prior to tapentadol PR treatment, as well as scrutinized those patients, either benefiting from a medium/high dose tapentadol PR monotherapy or a combination therapy (medium dose tapentadol PR + pregabalin). Patients and Methods: The statistical approach included data of a previously published randomized, double blind, phase 3b study which compared the effectiveness and safety of tapentadol PR versus a combination of tapentadol PR and pregabalin. In total, 46 clinical parameters were included in the statistical prediction models which were applied separately either to 50 patients who already responded well during the titration period (i.e. medium dose tapentadol PR) or to 261 patients with in the comparative treatment period (i.e. monotherapy [high dose tapentadol PR] or combination therapy [medium dose tapentadol PR/pregabalin]). Results: The first statistical model identified three co-variables (NRS-3, PDQ, SQ) with predictive effects on patients responding well (“optimal responders”) to a medium dose tapentadol PR titration. Those patients presented low baseline pain intensity scores, good sleep quality and high painDETECT scores. The second statistical model identified eight co-variables (PDQ, numbness, SF-12 MCS, SF-12 PCS, VAS, HADS-A, HADS-D, SQ) with predictive effects on patients responding to high dose tapentadol PR monotherapy versus a combination therapy (tapentadol PR + pregabalin). The high dose tapentadol PR responders indicated high painDETECT scores, little numbness and a good mental health status. Whereas, the combination therapy (tapentadol PR + pregabalin) responders were characterized by severe sleep disturbances and little anxiety. Conclusion: The statistical analysis characterized chronic low back pain patients and identified factors contributing to a treatment response. Thus, this retrospective statistical algorithm represents an elegant method, which may contribute to future strategies towards a more individualized and improved mechanism based pain therapy.